A Comparison of Biocolloid and Colloid Transport in Single, Saturated Rock Fractures - Qu, Junlei (My University, 2010)
To obtain a better understanding of groundwater contamination, experiments of biocolloid and colloid transport in single, saturated fractures are conducted to have research in contaminants transport in fractured media. Hydraulic tests and solute tracer tests were conducted to characterize fractures. Due to the relatively large volume in the recirculation system, a back-calculation is employed in the analysis of tracer tests.
E. coli RS-2GFP tracer tests were conducted on three fractures at specific discharges of 0.1, 1 and 10 cm/min. With higher specific discharges, the percent recovery is higher in F2 and F3, as well as the colloid experiments, which is likely due to higher specific discharges providing biocolloids less opportunity to attach to the fracture walls. But this did not occur in F1, which is likely due to the smaller aperture size.
Comparing the synthetic replicas with real fractures in similar specific discharges, recovery of biocolloid was smaller than colloid. In colloid tracer tests, higher recovery appeared in the fractures with larger aperture field, but this is not clearly seen in biocolloid tracer tests. These indicate that the biological properties of bacteria, and the difference of fracture region and the tortuosity influence the transport.
Keywords: Civil Engineering; Civil Engineering